Integration Of Discovery Learning with A Deep Learning Approach Through Simple Demonstrations to Enhance Seventh-Grade Students’ Understanding of Science Concepts - Ikhwan Hidayat Hiyahara; Sitti Saenab; Biyatmiati Biyatmiati (MISOOL: Jurnal Pendidikan Dasar, 2026)
This study aimed to describe the development of Grade VII students’ conceptual understanding of science through the integration of Discovery Learning, Indonesia’s Deep Learning approach, and simple demonstrations. A Classroom Action Research design was conducted in three cycles consisting of planning, implementation, observation, and reflection stages. The intervention involved all 34 students in Class VII I at SMP Negeri 33 Makassar, Indonesia. However, the primary longitudinal quantitative analysis was conducted using data from 20 students who completed all six research meetings. The remaining 14 students were excluded from the longitudinal analysis because their data were incomplete due to illness, school activities, or absences. Data were collected using a 10-item multiple-choice conceptual understanding test and classroom observation records, then analyzed through descriptive quantitative and qualitative procedures. The mean scores increased from 58.75 in Cycle I to 66.50 in Cycle II and 71.50 in Cycle III. Classical mastery improved from 10% to 20% and 25%, while achievement across conceptual understanding indicators increased from 61.96% to 72.32% and 78.93%. These findings indicate descriptive improvements in students’ conceptual understanding, however, the 85% mastery criterion was not achieved.